Hubungan Motivasi Kerja terhadap Perilaku Caring Perawat di Ruang Rawat Inap Rumah Sakit Jiwa Tampan Provinsi Riau - Siti Khodijah; Erna Marni (STIKes Hang Tuah Pekanbaru, 2014)
Caring is a comprehensive phenomenon that can affect the way people think, feel and have a relationship with fellow. Caring behavior can be realized due to lack of motivation of both internal and external. This research aims to determine the relationship of work motivation on nurses caring behaviors in the patient room at Tampan Pshyciatric Hospital, Riau Province. Type a descriptive study with cross sectional correlation. Sampling technique with non-probability sampling sample size by 56 respondents, measuring tools in the form of questionnaires and observation sheets. The analysis used is univariate and bivariate analysis using chi-square test. The result shows revealed a significant relationship between work motivation on nurse caring behaviors in the patient room with (p value = 0.001). Expected to Section Diklit and nursing fields section to hold trainings for nurses related to caring behavior in implementing nursing care so as to improve the quality of nursing care to clients